Clinical significance and effect of AEG-1 on the proliferation, invasion, and migration of NSCLC: a study based on immunohistochemistry, TCGA, bioinformatics, in vitro and in vivo verification - Zhang, Yu (Oncotarget, 2017)
BACKGROUND: Astrocyte elevated gene-1 (AEG-1) is related to the tumorigenesis and deterioration of different cancers, including non-small cell lung cancer (NSCLC). However, the effect of AEG-1 in NSCLC remains unclear. In this study, we aimed to investigate the clinical significance and effect of AEG-1 on biological function of NSCLC. RESULTS: AEG-1 was significantly overexpressed in NSCLC tissues and closely correlated to the deterioration of NSCLC based on tissue microarray, TCGA database and meta-analysis. After knock-down of AEG-1, the proliferation, migration and invasion of NSCLC cells were all inhibited, and the tumorigenic and angiogenic ability of NSCLC cells were weakened. Furthermore, the AEG-1 co-expressed genes were significantly related to AMPK signaling pathway based on bioinformatics approaches. MATERIALS AND METHODS: A tissue microarray, the Cancer Genome Atlas (TCGA) database, as well as a meta-analysis were performed to analyze the relationship between AEG-1 and the clinicopathological parameters of NSCLC. Furthermore, immunocytochemistry, Western blot analysis, scratch assay, colony formation assay, Transwell migration and invasion assay and the chick embryo chorioallantoic membrane (CAM) model were conducted to explore the effect of AEG-1 on NSCLC in vitro and in vivo. Additionally, bioinformatics analyses were carried out to assess the potential pathways and networks of the co-expressed genes of AEG-1. CONCLUSIONS: AEG-1 is positively activated in the tumorigenesis and deterioration of NSCLC. We hypothesize that AEG-1 could play an important role in NSCLC via AMPK signaling pathway. Inhibiting the expression of AEG-1 is expected to become a novel method in the therapeutic strategies of NSCLC.